A STOCHASTIC APPROXIMATION-ITERATIVE LEAST SQUARES ESTIMATION PROCEDURE - Kashmar, Ali (Iraqi Journal of Science, 2024)
We consider the general nonlinear regression problem . Asurvey of some classical methods and stochastic approximation procedures forestimating is first given. We solve the nonlinear regression problem byconsidering the optimal stochastic approximation procedure by [3],[4]. This leads usto introduce a new procedure , called "Stochastic Approximation Iterative LeastSquare Procedure" SA -ILS procedure. The new procedure is applied to a number ofnonlinear regression models. We report on the results of a simulation investigationwhich indicate that the new procedure is highly efficient with respect to the numberof observations required to obtain the parameter estimates for given regressionproblem.